Pengaruh Semangat Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Gaya Kepemimpinan Sebagai Variabel Moderating (Studi Kasus Pada CV. Maju Sejahtera Intimojopahit) - Ahmad fatur Rahman Sampurna jaya; Febriyanto; Dharmawan (Jurnal Manajemen DIVERSIFIKASI, 2025)
The aim of this research is to determine whether there is an influence of work morale and work environment on employee performance with leadership style as a moderating variable on CV. Maju Prosperous Inti Mojopahit. The role of employees is very important to the success or failure of the company. Problems related to performance are also a tragic issue for companies that program human resource problems. Success in performance depends on work morale, work environment, and leadership style. With less than optimal performance caused by a lack of work enthusiasm among employees and a poor work environment, as well as the implementation of a leadership style that is not wise enough, the results obtained are less than optimal. This research uses quantitative research; the sample in this research is 40 employees. The data collection technique uses a questionnaire, with data analysis using Validity Test, Reliability Test, Normality Test, Linearity Test, Homogeneity Test, MRA Interaction Test, R Determination Test, and Statistical Hypothesis Test. By using data processing program SPSS version 22, The research results show that work enthusiasm influences employee performance, the work environment influences employee performance, and leadership style as a moderation variable is able to strengthen work enthusiasm for employee performance at CV. Maju Sejahtera Inti Mojopahit and leadership style as a moderation variable are able to strengthen the work environment and employee performance at CV. Maju Prosperous Inti Mojopahit.